The Internationalization of the University: Opportunity for Institutional Strengthening - Miguel Cordero-Chavier (Ágora de Heterodoxias)
At present, university education has several challenges since the end of 2019 when the COVID-19 pandemic was declared. The reality has changed. This situation has caused the Houses of Studies to reformulate themselves. They are not only protagonists in the transformation of the regions in which they are located, but also they must project themselves beyond regional and national borders, i.e., they must internationalize. Universities have bodies through which they manage international affairs, such as Rectorates, Vice Rectorates, Secretariats or Directorates. They also coordinate and supervise strategies for relations with institutions in other nations.